IMPLEMENTATION OF PRINCIPAL COMPETENCE IN EDUCATIONAL RESOURCE MANAGEMENT - Agusalim, Agusalim; Saleh, Rachman; Riniati, Wa Ode; Yusnan, Muhammad; Farisatma, Farisatma (JURNAL EDUSCIENCE, 2025)
Purpose – This study aims to identify the challenges faced by school principals in managing resources, as well as formulate strategies or recommendations that can support increasing the effectiveness of school management.Methodology – The research method uses a study approach to analyzing research journal trends using bibliometric mapping that allows policy makers, including school principals, to understand the development of innovations that can be applied in school management. Data analysis in this study was carried out on 650 documents that had been collected and selected based on relevance to the research topic. After the initial processing stage, the data was further analyzed using VOSviewer, a bibliometric software that allows visualization of relationships between researchers, institutional collaboration, and mapping of keywords that often appear in the documents analyzed.Findings – The results of this study indicate that the implementation of principal competencies in managing educational resources plays an important role in improving the effectiveness of school management and the quality of learning. The use of technology, data analysis, and performance-based approaches are the main focus in educational leadership strategies. The contributions of various countries show that this issue is receiving global attention, with best practices that can be adapted to improve school competitiveness.Contribution – With a data-based approach, principals can optimize teaching staff, facilities, and curriculum to create a more adaptive and innovative learning environment.